Meta Analysis the Effect of Acupunctur Therapy and Ultrasound Therapy to Reduce Pain Caused by Carpal Tunnel Syndrome - Noer, Afifah; Rahardjo, Setyo Sri; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Carpal tunnel syndrome is a condition of health problems in the form of pain, numbness, and tingling that occurs in a person's hands. This sensation can be felt in the thumb, index finger, middle finger, and 1/2 ring finger on the radial side, this occurs when the median nerve that passes through the carpal tunnel at the wrist is compressed or compressed. This study aims to estimate the effect of acupuncture therapy and ultrasound therapy on reducing pain in carpal tunnel syndrome cases.Subjects and Method: This was a systematic review and meta-analysis conducted using PRISMA flow diagrams. Article searches through journal databases include: PubMed, Science Direct, Scopus, Google Scholar, Springer Link, Hindawi, BMC. The PICOs of this study were, Population: carpal tunnel syndrome sufferers, Intervention: acupuncture therapy and ultrasound therapy, Comparison: no acupuncture and ultrasound therapy, Outcome: pain reduction. Using search keywords: (“acupuncture” OR “acupuncture therapy”) AND (“carpal tunnel syndrome” OR “cts”) AND (“ultrasound” OR “ultrasound therapy”) AND (“randomized controlled trial”) AND (“ acupuncture for carpal tunnel syndrome”) AND (“ultrasound for carpal tunnel syndrome”). Inclusion criteria were full paper articles with Randomized Controlled Trial (RCT) research method, the relationship measure used was Mean SD, the intervention given was acupuncture and ultrasound, study subjects were aged 18-85 years. Eligible articles were analyzed using the Revman 5.3 app.Results: Meta-analysis of 16 articles showed acupuncture treatment outcome of -0.34 units compared with other interventions or no intervention (SMD -0.34; 95% CI= -0.83 to 0.16; p=0.180), I2=78%, and treatment outcome. ultrasound as much as -0.76 units compared with other interventions or no intervention, and statistically significant value (SMD -0.76; 95% CI= -1.37 to -0.16; p=0.001), I2= 92%.Conclusion: Acupuncture therapy and ultrasound therapy have an effect on reducing pain in cases of carpal tunnel syndrome.Keywords: Acupuncture, ultrasound, carpal tunnel syndromeCorrespondence: Afifah Noer. Masters Program in Public Health. Universitas Sebelas Maret, Jl.Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: Afifahnoer97@gmail.com. Mobile: 085601564681.Indonesian Journal of Medicine (2021), 06(04): 399-411https://doi.org/10.26911/theijmed.2021.06.04.06